A METHOD OF NONDESTRUCTIVE TESTING AS A WAY TO INCREASE ENERGY EFFICIENCY AND ENERGY SAFETY - Akhmad Borisovich Chapaev; Hasen Mihaylovich Karezhev; Artur Muhamedovich Sohrokov (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the question of definition of ways of increase of efficiency and quality control of construction works. They also addressed the issue of industrial safety. As an effective method of quality control of construction works and ensuring of industrial safety at industrial facilities is proposed the method of nondestructive testing. It is concluded that the method of thermal imaging inspections at various stages of the work such as design, prefabrication and precast construction, ensures quality control of construction works.